PENGGUNAAN STRATA TAJUK OLEH SATWA BURUNG DI DESA LORULUN KECAMATAN WERTAMRIAN, KABUPATEN KEPULAUAN TANIMBAR - Patty, Keiji; Pattinasarany, Cornelis Katje; Latupapua , Lesly (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This research aims to determine the use of canopy strata for birds and determine bird activity based on the use of canopy strata in Lorulun Village, Wertamrian District, Tanimbar Islands Regency. Bird watching in Lorulun Village uses the point count method which is made in five plots. To collect vegetation structure data vertically, namely using a canopy stratification approach, the technical implementation is by recording the types of birds found. The data obtained in this research was then analyzed descriptively qualitatively and quantitatively. The results of the research carried out were that there were 20 types of bird species found at the research location with distribution in strata A, there were 7 species of birds, Strata B, there were 7 species of birds, Strata C, there were 8 species of birds, Strata D, there was 1 species of birds. birds, Strata E there are 2 types of bird animals in the use of per strata, while in the use of vegetation strata there are bird species that use more than one stratum, 16 types of bird animals and activity patterns of bird species in each stratum include: rest activities, social activities and activities. Eat. Including the activity patterns of bird species in each strata, including: resting activities, social activities and eating activities.